Prevention of low density lipoprotein aggregation by high density lipoprotein or apolipoprotein A-I. - JC Khoo; E Miller; P McLoughlin; D Steinberg (Journal of Lipid Research, 1990)
We have shown previously that low density lipoprotein (LDL) subjected to vortexing forms self-aggregates that are avidly phagocytosed by macrophages. That phagocytic uptake is mediated by the LDL receptor. We now show that LDL self-aggregation is strongly inhibited (80-95%) by the presence of high density lipoprotein (HDL) or apolipoprotein (apo) A-I. Another type of LDL aggregation, namely that induced by incubation of LDL with phospholipase C, was also markedly inhibited by HDL or apoA-I. The aggregation of LDL induced by vortexing was not inhibited by 2.5 M NaCl, and apoA-I was still able to block LDL aggregation at this high salt concentration, strongly suggesting hydrophobic interactions as the basis for the effect of apoA-I. The fact that apoA-I protected against LDL aggregation induced by two apparently quite different procedures suggests that the aggregation in these two cases has common features. We propose that these forms of LDL aggregation result from the exposure of hydrophobic domains normally masked in LDL and that the LDL-LDL association occurs when these domains interact. ApoA-I, because of its amphipathic character, is able to interact with the exposed hydrophobic domains of LDL and thus block the intermolecular interactions that cause aggregation.